Kern-oorwegings in die besinning oor die rol van die (NG) Kerk in Suid- Afrika se grondhervormingsdebat - van Niekerk, Anton (Stellenbosch Theological Journal, 2020)
Core considerations in the reflection on the role of the (NG) Church in South Africa's land reform debate This article deals with the question as to whether the church (the Dutch Reformed Church in particular) ought to become involved in the current (2019) debate about land reform (particularly land expropriation without compensation) in South Africa. The author defends the position that such involvement is, for the church, desirable and even unavoidable. Four key elements of such involvement are identified and analysed. The first is the issue of human dignity, which is a key aspect of the message of the gospel. The second aspect is (possible) leadership. Here it is argued that the church can facilitate, but not in a traditional leadership role. Much attention is, thirdly, paid to the moral aspects of the debate. Finally, in terms of the “how”-question relating to the church's involvement, dialogue is proposed.